Antioxidant Enzyme (IntechOpen, 2021)
Free radicals are constantly formed in living cells and removed by antioxidant defenses. Antioxidant enzymes are the main line of defense against free radicals in animal and plant cells. Uncontrolled generation ROS are involved in a number of human disease states, including diabetes and cancer due to disturbance in cellular and molecular processes including cell growth, differentiation and proliferation. When cells are exposed to oxidative stress a defense system endorses the expression and regulation of number of antioxidant enzymes as a defense mechanism to protect them from the damage induced by free radicals. Based on this fact, the book "Antioxidant Enzymes" was designed to overview the importance of the antioxidant enzymes in human and plant cells against toxic free radicals, their relationship with several pathophysiologic processes and their possible therapeutic application.